Laboratory assessments and field tests in Predicting competitive performance of swimmers - Zuoziene, I. J.; Poderys, J. (Education. Physical training. Sport, 2012)
Research background and hypothesis. The assessments of functional fitness of swimmers includes the analyses of the physical, physiological and biomechanical indices for scientific purposes. The hypothesis is that dynamical parameters registered while performing field testing tasks could be more informative than laboratory assessments in predicting the performance abilities. The aim of the study was to compare the informativeness of field tests and laboratory assessments in predicting the possible performance of athletes in the 50 m distance. Research methods. Twelve professional swimmers took part in three testing procedures. First, each participant performed a test in water to establish the traction force parameters and indices of muscle power and anaerobic capacity. Second, the subjects performed a control 50 m freestyle swim the best they could. Third, the indices of relative muscle power during jumping tasks, anaerobic capacity, and functional indices of cardiovascular system were assessed during laboratory testing. Research results. Significant correlation was found between the results in 50 m swimming and traction forces while performing testing tasks in water or out of water with arms or arms and legs together. However, there was no statistically significant correlation between the results in swimming and the height of vertical jump. Still there exists significant correlation (p < 0.05) between the speed and force components as well as fatigability index and the competition result (r = -0.47; r = 0.56 and r = 0.67, respectively). Discussion and conclusions. Dynamical parameters measured in the swimming pool while performing field tests are more suitable than the data of laboratory research for predicting the results of swimmers in the 50m freestyle swim. The vertical high jump tests and indices of ECG allow distinguishing the factors limiting the working capacity of athletes.